Potential of nanoformulations in malaria treatment - Chaves, Janaina Braga; Portugal Tavares de Moraes, Bianca; Regina Ferrarini, Stela; Noé da Fonseca, Francisco; Silva, Adriana Ribeiro; Gonçalves-de-Albuquerque, Cassiano Felippe (Frontiers in Pharmacology, 2022)
Malaria is caused by the protozoan Plasmodium sp and affects millions of people worldwide. Its clinical form ranges from asymptomatic to potentially fatal and severe. Current treatments include single drugs such as chloroquine, lumefantrine, primaquine, or in combination with artemisinin or its derivatives. Resistance to antimalarial drugs has increased; therefore, there is an urgent need to diversify therapeutic approaches. The disease cycle is influenced by biological, social, and anthropological factors. This longevity and complexity contributes to the records of drug resistance, where further studies and proposals for new therapeutic formulations are needed for successful treatment of malaria. Nanotechnology is promising for drug development. Preclinical formulations with antimalarial agents have shown positive results, but only a few have progressed to clinical phase. Therefore, studies focusing on the development and evaluation of antimalarial formulations should be encouraged because of their enormous therapeutic potential.